2022
DOI: 10.1108/ajb-02-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

The integrated effect of Kaizen and innovation culture on the police performance: an empirical investigation

Abstract: PurposeLimited use of Kaizen practices in police agencies, together with very few studies that investigated the link between it and police performance, gives a gap and good indication to conduct this study. Thus, this study seeks to explore and examine this relationship through the lens of innovation culture as a mediating factor.Design/methodology/approachThis paper was based on a survey with 352 effective participants, including the head section officers of the Dubai Police in the UAE. A structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…According to the (Hashim, Zubir, Conding, Jaya, & Habidin, 2012), there was a positive and direct relationship between the kaizen event and the innovation performance in Malaysia's automotive industry (Hashim et al, 2012). One of the goals of Kaizen is to develop people's creativity and curiosity to lead them to create value for customers (Alosani & Al-Dhaafri, 2022). In order to ensure performance change after implementing kaizen, conducting a survey is a very effective tool.…”
Section: Discussionmentioning
confidence: 99%
“…According to the (Hashim, Zubir, Conding, Jaya, & Habidin, 2012), there was a positive and direct relationship between the kaizen event and the innovation performance in Malaysia's automotive industry (Hashim et al, 2012). One of the goals of Kaizen is to develop people's creativity and curiosity to lead them to create value for customers (Alosani & Al-Dhaafri, 2022). In order to ensure performance change after implementing kaizen, conducting a survey is a very effective tool.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement and structural model were examined to evaluate the hypotheses in the theoretical model. PLS-based SEM was preferred in this study due to its ability to explain the relationships between variables (Alosani and Al-Dhaafri, 2022; Urbach and Ahlemann, 2010). SEM was deemed more appropriate as it allowed the researchers to test both direct and indirect effects simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers believe that organisational processes can be continuously improved through simple and effective methods in Kaizen (Alosani and Al-Dhaafri, 2022). Through the application of Kaizen, wastage in any organisation is identifiable, and energy consumption is reduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2022). Moreover, researchers have concluded that Kaizen is one of the simplest and most continuous methods that are cost-effective, uses minimal resources and helps organisations reach their goals in the long term, leading to a sustainable competitive advantage (Alosani and Al-Dhaafri, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation